Penilaian Autentik Pelajaran Pendidikan Agama Islam dan Budi Pekerti: Penilaian Autentik Pelajaran Pendidikan Agama Islam dan Budi Pekerti - Teguh Imam Triono Teguh Imam Triono; Asmuki Asmuki (Fakultas Tarbiyah Institut Agama Islam Ngawi, 2023)
Authentic assessment is an evaluative approach rooted in data that mirrors students' competencies acquired throughout the learning process, encompassing not only their final learning outcomes. This evaluation encompasses three key domains: knowledge proficiency, skill proficiency, and attitude competency. The research in question is a descriptive qualitative study conducted against the backdrop of the 2013 curriculum transformation into an independent curriculum at SMAN 1 Asembagus. Even under the independent curriculum, the continued utilization of authentic assessment remains pertinent. The research cohort comprised both teachers specializing in Islamic Education and Character, as well as students in grades 10 and 11. Furthermore, the research sought to outline the practical application of authentic assessments within the domains of Islamic Religious Education and Character Education. The data collection process involved a combination of observation, interviews, and document analysis. To ensure the data's credibility, a triangulation method was employed, merging the insights from observations, interviews, and documentation. The study's findings indicate that the implementation of authentic assessment in the context of Islamic Education and Character subjects at SMAN 1 Asembagus has been largely successful, despite a few challenges during its execution that were effectively surmounted.